Application of nisin as a potential drug candidate for electrochemotherapy - Michel, Olga; Lekešytė, Barbora; Malyško-Ptašinskė, Veronika; Morozas, Arnoldas; Malakauskaitė, Paulina; Mickevičiūtė-Zinkuvienė, Eglė; Želvys, Augustinas; Ivaška, Justinas; Kulbacka, Julita; Novickij, Vitalij (Frontiers in Oncology, 2025)
IntroductionElectroporation (EP) is a technique that transiently increases the permeability of the cell membrane through the application of high-voltage electric pulses, facilitating the intracellular delivery of therapeutic agents or the selective ablation of cells. Combination of EP with cytotoxic drugs—most commonly bleomycin or cisplatin—is termed electrochemotherapy (ECT), which markedly enhances drug efficacy and permits targeted, locally controlled treatment with reduced systemic exposure. Currently, in addition to microsecond (µs) pulses, nanosecond (ns) pulses are being proposed for clinical use to mitigate certain ECT-associated side effects. However, achieving robust permeabilization with nsPEF typically requires higher electric fields. Nisin is a polycyclic antibacterial peptide with anticancer potential that can be leveraged in this context.MethodsTo date, the permeabilizing properties of nisin have been employed alongside an external electric field exclusively in bacterial systems and artificial membranes. In this study, we investigated the impact of nisin on membrane permeabilization, resealing, and viability of 4T1 breast cancer cells exposed to microsecond and nanosecond electric pulses of varying field strengths and pulse frequencies.ResultsAcross all experimental conditions, nisin reduced the threshold voltage necessary for effective permeabilization and increased treatment-induced cell mortality.DiscussionSince nisin is non-toxic by itself, it represents a promising candidate for electrochemotherapy, potentially supporting its wider clinical application in the future.